Trichobezoar as an Unusual Cause for Iron Deficiency Anemia: A Rare Case Report - Mohamad Moamen Almouallem; Majd Hanna; Nafiza Martini; Ahmad Alfarouh; Rand Mousseli; Maysam Yaldany; Jaber Mahmod (Clinical Case Reports)
ABSTRACT Trichobezoars are conglomerations of undigested foreign materials within the gastrointestinal tract (GIT). They are most commonly observed in young girls. Trichobezoars typically lodge in the stomach, but can extend further into the intestines in a condition called Rapunzel syndrome. The current patient, a young girl, complained of abdominal pain accompanied by diarrhea. She also had a history of bile vomiting 1 month prior and an abnormal craving for mud (PICA). Trichobezoars are often linked to hair‐pulling disorders or other mental health conditions, and symptoms can be vague for years before progressing to nausea, vomiting, weight loss, and even iron deficiency anemia. Treatment involves removing the hairball and addressing any underlying psychological issues. In the current case, we aimed to elucidate the diagnosis, management, and unique features of gastrointestinal tract trichobezoars, which are uncommon causes of gastrointestinal distress and iron deficiency anemia (IDA).